Genealogia literária em A estranha nação de Rafael Mendes, de Moacyr Scliar - Glauber Pereira Quintão (2011)
The novel of Moacyr Scliar, A estranha nação de Rafael Mendes, 1983, shows in this context, opportunity to the study that can be seen like a literary genealogy of the creation of its protagonist Rafael Mendes. This genealogy uses important narrations resources of literary theory as well as your relation with the history and the cultural memory. This research attempted mark the particular mechanisms like analyses/elaboration about the concept which was adopted to call literary genealogy. By using this expression it seeks to detach its relation with the traditional meanings of genealogy that is historically used like politics mechanisms of alliance and inserting able individual parentage or supposedly noble blood earn, in fiction one critic in the same time that escape hierarchy relations that attempt somewhat, think about one supposed natural order or divinely given. The literary genealogy in the novel of Scliar builds the history of generations and generations of Rafael Mendes ancestors who through irony is able to deconstruction of fundamental mechanisms.